PENINGKATAN KEMAMPUAN MEMBEDAKAN FAKTA DAN OPINI MELALUI MEDIA ZONA DETEKTIF BERBASIS PROYEK POSTER SISWA KELAS DASAR - Willis Niki Suryadita; Dede Nuraida; Sri Rahayu Puji Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This Classroom Action Research (CAR) aims to improve the ability to distinguish between fact and opinion sentences among fifth-grade students through the implementation of the "Detective Zone" media based on a poster project. The subjects of this study were 21 fifth-grade students of UPT SD Negeri Kebonsari 3. The research was conducted in April 2026 across two action cycles. Data collection utilized learning achievement test instruments to measure cognitive abilities and observation sheets to measure student activity. The results showed a significant improvement in both the learning process and learning outcomes. In the Pre-Cycle condition, students' classical mastery reached only 45%. After implementing the action in Cycle I using the poster project, classical mastery increased to 60%. Furthermore, after refining the action in Cycle II using a combination of the "Detective Zone" game media and the poster project, students' classical mastery soared sharply to reach 86%. Qualitatively, students' learning activity and enthusiasm also increased; students became more focused, actively collaborated in groups, and became skilled in analyzing exposition texts. Based on these results, it can be concluded that the implementation of the poster project-based "Detective Zone" media is effective in improving the ability to distinguish facts and opinions among elementary school students.